2013
DOI: 10.1111/tbed.12067
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on aStreptococcus suisVaccine Using Recombinant Sao-L Protein Manufactured by Bioreactors as the Antigen in Pigs

Abstract: Streptococcus suis (S. suis) can be classified into 33 serotypes based on the structure of capsular polysaccharides. Recent research indicated that a new surface protein designated as Sao (surface antigen one) reacts with 30 serotypes of convalescent-phase sera during S. suis infections, which makes Sao a good potential antigen for developing S. suis vaccines. The objectives of this study were to produce recombinant Sao-L protein (rSao-L) from a strain of S. suis serotype 2 by a prokaryotic expression system i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…Bacteria were grown in brain-heart infusion (BHI) broth supplemented with 0.5% yeast extract (Difco Laboratories, Spark, MD, USA) at 37 °C. The rSao was expressed as previously described [19]. The size of PCR product from the S. suis strain BCRC 14750 (ATCC 43765) was 2013 bp.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria were grown in brain-heart infusion (BHI) broth supplemented with 0.5% yeast extract (Difco Laboratories, Spark, MD, USA) at 37 °C. The rSao was expressed as previously described [19]. The size of PCR product from the S. suis strain BCRC 14750 (ATCC 43765) was 2013 bp.…”
Section: Methodsmentioning
confidence: 99%
“…We previously demonstrated that immunization with recombinant Sao-L protein (rSao-L) from a strain of S. suis serotype 2 in pigs was able to increase antigen-specific antibody titers, the percentages of CD8 + and CD4 + /CD8 + double-positive T cells, and cross-protection against S. suis serotype 1 heterologous challenge [19]. Since weaning piglets are more susceptible to S. suis infections due to the stress associated with weaning, prepartum immunization in sows may convey passive immunity to piglets and provide protection.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, Hsueh et al [25] established ELISA using Sao-L and Sao-M for detecting titers of Sao-L-specific total IgG and Sao-M-specific total IgG. In the present study, Sao-M was used to establish PPA-ELISA for the diagnosis of S. suis infection.…”
Section: Discussionmentioning
confidence: 99%
“…JF 810176. The primer of the Sao-M gene was: Sao-F: GCGGGATCC ATGAATACTAAGAAATGGAG and Sao-R: CAGAAGCTTGAACTA ATTTACGTTTACGTG [25] . The forward and reverse primers contained BamH I and Hind III recognition sequences, respectively.…”
Section: Preparation Of Recombinant Sao-m Proteinmentioning
confidence: 99%
See 1 more Smart Citation